HUBUNGAN PERSEPSI MAHASISWA TENTANG METODEMENGAJAR DOSEN DENGAN MINAT BELAJAR MAHASISWA PRODI DIII KEBIDANAN STIKes PRIMA NUSANTARA BUKITTINGGI TAHUN 2015 TAHUN KE 1 DARI 1 TAHUN - Nova, Desri; Putri, Kartika Eka (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Approximately 20% - 30% of deaths of children under five age are caused by acute respiratory infections (ARI). The State Indonesia respiratory disease is still quite high, especially in children that was at toddler group .caused by risk factors that can increase the incidence of acute respiratory infection in infants were age <2 months, malnutrition, low weight born. Sosial population, density residential and incomplete immunization. Data West Sumatra Provincial Health Office, ARI occupy the top with a total of 203 750 cases in 2014. The purpose of this study was to determine the relationship of knowledge Mothers who have children with ARI. This type of research is descriptive research with cross-sectional design. The population in this study were mothers with young children who come to the public health center Kebun Sikolos Padang Panjan. Sampling technique with accidental sampling. This study using univariate and bivariate analysis technique with Chi-Square test at 95% trust level Î± = 0.05. Results of the study on 34 respondents mothers who have children in the health center Kebun Sikolos Padang Panjang, it was found that the percentage of ARI is higher among respondents with sufficient knowledge (61.8%) compared to respondents who are knowledgeable good (3%).And the results of the statistical test p-value 0.697 that while the alpha value of 0.05 means a p-value greater than the value of a then concluded there was no correlation with the mother's knowledge ISPA events in Padang Panjang Kebun Sikolos Health Center in 2015. Suggested to health officials at the health center Kebun Sikolos, Through Health Center to develop a program to improve nutrition in children under five point boost immunity in infants so they can avoid many diseases one of acute respiratory infections.